PENGARUH INFORMASI LABA, TOTAL ARUS KAS DAN KOMPONEN ARUS KAS TERHADAP HARGA SAHAM PADA PERUSAHAAN DAGANG YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mas’ut Mas’ut; Nurhasanah Sijabat (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2018)
This research aims to determine the influence of the accounting income, total cash flow and cash flow components that cash flow operating activities, investing and financing influence the stock price at the Wholesale sector trading companies listed on the Indonesia Stock Exchange in 2011-2015 partially and simultaneously. The independent variables were examined in this study is the accounting profit, total cash flow, cash flow operating activities, investing activities and cash flows aks current funding activities. Sampling was done by purposive sampling. Test equipment research use multiple linear regression model. Conclusions from the study were simultaneously or partially in this study showed no effect of the independent variable on the dependent variable. The result of determination shows that the variable accounting profit, total cash flow and cash flow component of cash flows from operating, investing and financing only able to explain the share price by 1.6% while the rest is influenced by other variables that are not discussed in this study.